The solution phase aggregation of graphene nanoplates - Krittayavathananon, A; Li, X; Sokolov, S; Batchelor-McAuley, C; Sawangphruk, M; Compton, R (Elsevier, 2018)
The occurrence of particle aggregation, especially for two-dimensional (2D) nanoparticles, in the solution phase is an important practical problem. Aggregation influences the materials’ properties and behavior. This work studies the re-stacking process of graphene nanoplates (GNPs) in colloids and suspensions by a simple and highly sensitive technique in which the current responses resulting from the impacts of individual and aggregated particles which bridge across two interdigitated gold microbands are detected. The magnitude of the steps in current varies as a function of time and yield clear in situ information regarding the formation of GNP aggregation.